Colchicine in atrial fibrillation: are old trees in bloom? - Zhan, Yujia; Yue, Honghua; Zhao, Xueshan; Tang, Juan; Wu, Zhong (Frontiers in Physiology, 2023)
Colchicine is a widely used drug that was originally used to treat gout and rheumatic diseases. In recent years, colchicine has shown high potential in the cardiovascular field. Atrial fibrillation (AF) is a cardiovascular disease with a high incidence. One of the most frequent complications following cardiovascular surgery is postoperative atrial fibrillation (POAF), which affects patient health and disease burden. This article reviews the research status of colchicine in AF and summarizes the relevant progress.Colchicine is an ancient drug. It has been extensively used to treat gout and rheumatic diseases for